Fenomena Halo Effect Terhadap Hijaber Pengguna Aplikasi Kencan - Maudy Bunga Rosmita Saragih (Universitas Muhammadiyah Sumatera Utara, 2023)
This research is based on the film Tinder Swindler which tells the story of a con artist who ensnares his victims through a dating app by giving a good impression. This study extends previous research by examining how hijabers prioritize the information listed on dating application profiles compared to the facial profiles used. Methods This research uses a post-postivist paradigm with a qualitative approach. Participants in this study consisted of 8 participants. This research uses in-depth interviews both offline and online. In addition to interviews, data collection was carried out by means of a literature study. The results of this study indicate that trust will be given when individuals feel interested and feel they have the same thing in common. For hijabers who are already willing to get married or not, they think that their background, similarities to each other, and all the information written on a dating app profile gives a first impression and therefore affects how users perceive other qualities about that person. The phenomenon of the halo effect can be a boomerang for individuals who do not seek clear information related to new people they meet.